Reduction of NOX concentrations in boiler flue gas by injecting selective reagents - Buinevičius, Kestutis; Puida, Egidijus (Journal of Environmental Engineering and Landscape Management, 2005)
Present EU regulations promote search for efficient means of reducing environmental pollution caused by fuel‐burning equipment. Primary means of NOx reduction are of a limited efficiency. The aim of this study is investigation and development of Selective Non‐Catalytic Reduction (SNCR) for NOx Control. This method can be applied in the existing boilers that have no external flue gas cleaning equipment, and that is the main advantage of the method. Experimental investigation of the influence of various reagent solutions on NOx concentration was carried out in a stand simulating a boiler furnace. Reagents and their operation conditions were selected, desirable efficiency of SNCR method was determined. The experimental results indicated positive application perspectives of this method. Reduction of NOx concentration by 40 % was reached. It was determined that improperly selected SNCR technology can even increase NOx concentration. Article in Lithuanian. Katilų degimo produktuose susidarančių NOx koncentracijų mažinimas, įpurškiant selektyviųjų reaktyvių Santrauka. ES normos skatina ieškoti efektyvių priemonių atmosferos taršai iš kurą deginančių įrenginių sumažinti. Pirminės NOx mažinimo priemonės yra riboto veiksmingumo. Darbas skirtas NOx selektyviajam nekatalitiniam valymui (SNKV) tirti ir tobulinti. Metodo privalumas ‐ gali būti taikomas esamuose katiluose be išorinių valymo įrenginių. Stende, imituojančiame katilo kūryklą, atlikti įvairių įpurškiamų tirpalų įtakos NOx koncentracijai eksperimentiniai tyrimai. Parinkti reaktyvai, jų naudojimo sąlygos ir nustatytas tikėtinasis SNKV metodo efektyvumas. Tyrimai parodė šio metodo taikymo perspektyvas, NOx sumažėjo 40%. Nustatyta, kad netinkamai parinkus SNKV technologiją, NOx išmetimai gali net padidėti. Reikšminiai žodžiai: azoto oksidai, selektyvusis nekatalitinis dūmų valymas, NOx redukcija, degimas. First Published Online: 14 Oct 2010